Nationwide, population-based study of prostate cancer stage migration between and within clinical risk categories. (October 2014) - Ohmann, Erin L.; Loeb, Stacy; Robinson, David; Bill-Axelson, Anna; Berglund, Anders; Stattin, Pär
Abstract Objective. In countries with widespread prostate cancer screening there has been strong stage migration, but little is known about changes within clinical risk categories. Such data are important for the proper interpretation of studies that recruited cases in an earlier era. The purpose of this study was to examine stage migration between and within clinical risk categories. Material and methods. Using the population-based National Prostate Cancer Register (NPCR) of Sweden, changes in the distribution of prostate-specific antigen (PSA), Gleason score, tumor stage and volume overall between and within clinical risk categories were examined in 120 228 prostate cancer cases diagnosed from 1998 to 2011. Results. Between 1998 and 2011, there was a two-fold increase in the proportion of low-risk prostate cancer (stage T1/T2, Gleason score 2–6 and PSA <10 ng/ml), from 14% to 28%, and more than a two-fold decrease in the proportion of metastatic disease, from 25% to 11%. The proportion of men in the low-risk category with T1c tumors increased two-fold, from 36% to 71%, and PSA levels between 4 and 6 ng/ml increased from 24% to 38%; T2 tumors decreased from 39% to 20% and PSA between 8 and 10 ng/ml decreased from 24% to 15%. The proportion of men with less than 25% of cores involved with cancer increased from 41% to 52% between 2003–2006 and 2007–2011. Conclusions. Low-risk cases today have substantially lower tumor volume and PSA levels than low-risk cases diagnosed in 1998, indicating that outcomes in studies that recruited cases in previous decades represent worst case scenarios.